Deregulation of Long Intergenic Non-coding RNAs in CD4(+) T Cells of Lamina Propria in Crohn’s Disease Through Transcriptome Profiling - Braga-Neto, Manuel B (J Crohns Colitis, 2020)
BACKGROUND: The aetiology of Crohn’s disease [CD] involves immune dysregulation in a genetically susceptible individual. Genome-wide association studies [GWAS] have identified 200 loci associated with CD, ulcerative colitis, or both, most of which fall within non-coding DNA regions. Long non-coding RNAs [lncRNAs] regulate gene expression by diverse mechanisms and have been associated with disease activity in inflammatory bowel disease. However, disease-associated lncRNAs have not been characterised in pathogenic immune cell populations. METHODS: Terminal ileal samples were obtained from 22 CD patients and 13 controls. RNA from lamina propria CD4(+) T cells was sequenced and long intergenic non-coding RNAs [lincRNAs] were detected. Overall expression patterns, differential expression [DE], and pathway and gene enrichment analyses were performed. Knockdown of novel lincRNAs XLOC_000261 and XLOC_000014 was performed. Expression of Th1 or Th17-associated transcription factors, T-bet and RORγt, respectively, was assessed by flow cytometry. RESULTS: A total of 6402 lincRNAs were expressed, 960 of which were novel. Unsupervised clustering and principal component analysis showed that the lincRNA expression discriminated patients from controls. A total of 1792 lincRNAs were DE, and 295 [79 novel; 216 known] mapped to 267 of 5727 DE protein-coding genes. The novel lincRNAs were enriched in inflammatory and Notch signalling pathways [p <0.05]. Furthermore, DE lincRNAs in CD patients were more frequently found in DNA regions with known inflammatory bowel disease [IBD]-associated loci. The novel lincRNA XLOC_000261 negatively regulated RORγt expression in Th17 cells. CONCLUSIONS: We describe a novel set of DE lincRNAs in CD-associated CD4(+) cells and demonstrate that novel lincRNA XLOC_000261 appears to negatively regulate RORγt protein expression in Th17 cells.